2017
DOI: 10.1111/ced.13219
|View full text |Cite
|
Sign up to set email alerts
|

Association of oxidative stress and dynamic thiol-disulphide homeostasis with atopic dermatitis severity and chronicity in children: a prospective study

Abstract: Both OS and impaired dTDH were found to be related to childhood AD. None of the OS parameters was associated with AD severity. dTDH is a possible diagnostic tool to predict AD chronicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 26 publications
0
21
0
1
Order By: Relevance
“…In detail, four studies were published in the 1990s, nine in the 2000s, and 21 in the last decade. Different geographical areas (and ethnicities) were not uniformly represented: 16 studies [17,18,23,24,27,[32][33][34][35][36][37][38]40,42,45,46] were performed in Eastern Asia (8 in Japan, 6 in Korea, 2 in Taiwan), nine [21,28,31,39,41,43,44,47,48] in Europe (3 in Russia, 2 in Germany, 1 in Finland, Italy, Norway, Switzerland), four [20,22,29,30] in Middle Eastern countries (3 in Turkey, 1 in Israel), two [25,26] in Southern Asia (Bangladesh, India), and one [49] in the United States of America. Another study [19] included patients from multiple Canadian and European centers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In detail, four studies were published in the 1990s, nine in the 2000s, and 21 in the last decade. Different geographical areas (and ethnicities) were not uniformly represented: 16 studies [17,18,23,24,27,[32][33][34][35][36][37][38]40,42,45,46] were performed in Eastern Asia (8 in Japan, 6 in Korea, 2 in Taiwan), nine [21,28,31,39,41,43,44,47,48] in Europe (3 in Russia, 2 in Germany, 1 in Finland, Italy, Norway, Switzerland), four [20,22,29,30] in Middle Eastern countries (3 in Turkey, 1 in Israel), two [25,26] in Southern Asia (Bangladesh, India), and one [49] in the United States of America. Another study [19] included patients from multiple Canadian and European centers.…”
Section: Resultsmentioning
confidence: 99%
“…In the serum of AD patients, significantly elevated levels of clusterin (correlated with disease severity) [24], significantly decreased levels of beta carotene [34], catalase [26], gamma tocopherol [39], glutathione peroxidase [26], Mg [30], NO [22], retinol [34], and levels of Cu similar to those of healthy controls [30] were found. Decreased also were, in AD patients, the serum total antioxidant capacity [38], serum disulphide, disulphide/native thiol ratio and disulphide/total thiol ratio [20], NO/melatonin ratio [22], nitrite/nitrate (NO x -) [45].…”
Section: Biomarkersmentioning
confidence: 99%
“…Moreover, disulfide to NT ratio was positively correlated and NT to TT ratio was negatively correlated with higher scores assessing atopic dermatitis severity. Authors have proposed that decreased disulfide level might result from rebound phenomenon to continue protective influence by facilitating the neutralization of oxidative state [74].…”
Section: Dermatologic Disordersmentioning
confidence: 99%
“…It also indicated that there was a decrease in the natural and total thiol levels in both acute urticaria and chronic spontaneous urticaria groups, thus suggesting that the activation of urticaria had an impact on the thiol/disulphide levels [9]. In a study carried out by Uysal et al, it has been reported that both oxidative stress and impaired thiol-disulphide balance are associated with childhood atopic dermatitis [18]. Although oxidative stress has been shown to be one of the factors responsible for the pathogenesis of psoriasis in various studies, its role is still unclear.…”
Section: Discussionmentioning
confidence: 94%
“…The thiol-disulphide balance has been researched in a limited number of dermatoses (urticaria, basal cell carcinoma, atopic dermatitis) until now [9,10,18]. Demirsen et al carried out research on 34 patients with basal cell carcinoma and a group of 30 healthy individuals to determine the thiol-disulphide balance.…”
Section: Discussionmentioning
confidence: 99%